Solo Sonographically Guided PCNL under Spinal Anesthesia: Defining Predictors of Success - Akbar Nouralizadeh; Hamid Pakmanesh; Abbas Basiri; Mohammad Aayanifard; Mohammad Hossein Soltani; Ali Tabibi; Farzaneh Sharifiaghdas; Seyed Amir Mohsen Ziaee; Naser Shakhssalim; Reza Valipour; Behzad Narouie; Mohammad Hadi Radfar (Scientifica)
Aim. Sonography has been brought in percutaneous nephrolithotripsy (PCNL) as an adjunct to or substitute for X-ray to restrict radiation exposure. This study was designed to investigate the possible predictors for the success of the solo sonographically guided PCNL. Methods. 148 consecutive cases were prospectively enrolled. All steps of PCNL were performed solely with sonography guidance under spinal anesthesia. Residual stones were evaluated the day after surgery using sonography and plain radiography. Results. The mean age was 46±15 years; 40% of kidneys had hydronephrosis. The mean stone burden was 504±350 mm2. The mean duration of surgery was 43±21 minutes. The early stone-free rate was 92% in inferior or middle calyceal stones, 89.5% in single pelvic stones, 81.5% in partial staghorn stones, and 61.9% in staghorn stones. The mean residual stone size was 13±8 mm. Logistic regression showed that a lower age and a larger stone burden significantly predicted positive residual stones. Fifteen percent of patients presented with grade I or II and six percent showed grade III complication based on Clavien classification. There was no cases of organ injury or death. Conclusion. Solo ultrasonographically guided PCNL under spinal anesthesia is feasible with an acceptable stone-free rate and complication rate.